Computational Study of Injection Molding Parameters to Minimize Shrinkage and Warpage Using the Taguchi Method - Dhiya’Uddin, Fachry; Bintara, Redyarsa Dharma; Suprayitno (Proceeding International Conference on Religion, Science and Education, 2022)
Injection molding is one of the processes for forming products from plastic materials using heat treatment and applying pressure into the mold (mold). The results products of injection molding must be of good quality with minimal shrinkage and warpage. The quality product of the injection molding process is affected by the parameters of the injection speed, injection pressure, injection time, and temperature on the barrel. The Taguchi method is one of the optimization methods that can be used to improve product quality. In Taguchi's robust design, a product will be designed to be strong and resistant to noise factors. This study aims to reduce shrinkage and warpage using Autodesk Moldflow simulation and the Taguchi method. In this study, there are 4 parameters with 3 levels each using the fractional factorial L9 Orthogonal Array Taguchi method and 4 times repetitions with consideration of the noise factor, the derivative of the sample also aims to determine fluctuations of data and obtain standard deviation values. The results of the study get the minimum shrinkage and warpage on the product, where the product resulting from optimization provides an increased (gain) S/N ratio between the initial design and the robust design. The optimization strategy found that IS= 50 cm/s, IP = 40 kg/cm2, IT = 5.5 seconds, TOB = 190?C, give the optimum shrinkage with -7.922 in S/N ratio or improve 0.736 compared from initial design, and give the optimum warpage with 3.718 in S/N ratio or improve 0.854 compared from the initial design.